2011
DOI: 10.1007/s00170-011-3744-1
|View full text |Cite
|
Sign up to set email alerts
|

Modelling micro geometrical profiles in fused deposition process

Abstract: Fused deposition modelling is an established additive manufacturing technique for creating functional prototypes from three-dimensional computer-aided design models. Despite of the potential advantages of this technology, surface roughness is a substantial problem and some attempts have been made to predict the average roughness R (a). As well known, the surface quality characterization of a part is not limited to R (a) but involves many other roughness parameters. The knowledge in advance of these parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(46 citation statements)
references
References 17 publications
2
44
0
Order By: Relevance
“…Since the orientation angle does not have fundamental dimensions (MLT), the initial surface roughness has been taken in the consideration in place of orientation angle. As in present context, only orientation angle affects the initial roughness as layer thickness is constant as found by previous studies [7][8][9], i.e. R ai = f (藳).…”
Section: Appendix a Appendix-imentioning
confidence: 62%
See 1 more Smart Citation
“…Since the orientation angle does not have fundamental dimensions (MLT), the initial surface roughness has been taken in the consideration in place of orientation angle. As in present context, only orientation angle affects the initial roughness as layer thickness is constant as found by previous studies [7][8][9], i.e. R ai = f (藳).…”
Section: Appendix a Appendix-imentioning
confidence: 62%
“…Vasudevarao et al [7] optimized various process parameters of FDM and found maximum impact of layer thickness and orientation angle on surface roughness while model temperature, air gap and road width have least influence. Boschetto et al [8] proposed a geometrical model to predict the surface roughness based on layer thickness and orientation angle while neglected the significance of model and support filling methods. The decrease in layer thickness reduces surface roughness but it further increases build time and thus adaptive slicing technique has been utilized by Thrimurthulu et al [9].…”
Section: Introductionmentioning
confidence: 99%
“…The popularity can be attributed to the availability of several affordable 3D printers. This affordability combined with high material usage efficiency has put FDM as a forefront technology with great potential in several industrial sectors [9], mould fabrication [10] and design of bio-medical devices [11] and tissue engineering [12].…”
Section: B Fused Deposition Modeling Technology In Briefmentioning
confidence: 99%
“…It was demonstrated that prediction of the surface roughness of FDM parts can be performed through comparison between measured data and computed values. Boschetto et al [17,18] proposes a new model to geometrically describe the roughness profile of FDM parts which only depends on two process parameters, layer thickness and stratification angle, and the effect of other parameters such as model filling, tilting are leading to a distortion of the peaks. Statistical tests show a good accordance with predicted values for the made assumptions and the calculated roughness parameters.…”
Section: Related Workmentioning
confidence: 99%